Queer voices from the locker room - McGivern, Cu-Hullan Tsuyoshi; Miller, Paul Chamness (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2017)
The editors intended for this volume to provide queer and ally athletes a space to have a voice and share the experiences that have been significant in their identity as an athletic member of the LGBT+ community. To that end, this book is a collection of autobiographical short stories of LGBT+ athletes and their experiences in sports and athletics, some who are publicly out and some who are not. Based on the narratives collected, the book is organized around themes that illustrate various perspectives and the power that sport can play in 1) finding one's true identity, 2) bridging communities, and 3) challenging gender norm stereotypes.The goal of this book is to help change the expectations of what it means to be a successful athlete and promote greater inclusivity of LGBT athletes. Providing the space for these voices to be heard will help to pave the way for a non-discriminating sporting environment, allow LGBT+ athletes to focus on their given sport without any distractions, and enable these athletes to live an authentic life without having to hide their true identity.
Keywords: Lesbian athletes -- Biography.; Gay athletes -- Biography.; Transgender athletes -- Biography.; Bisexual athletes.; elektronické knihy; Biographies.; Social Science -- LGBTQ+ Studies -- General.; LGBTQ+ Studies, topics.; Relating to LGBTQ+ people.; electronic books